Impact of the Workplace Environment on Employee Productivity - K.C., Harendra (Journal of Educational Research and Innovation, 2024)
The working environment plays a crucial role in an organization and has many employee issues. Increasing productivity can be achieved by creating a conducive working environment within the organization. The study investigates the impact of the working environment on employee productivity in Birendranagar, Surkhet, focusing on supervisor support, good relations with coworkers, training and development, and incentives and recognition plans. Adopting a positivist approach, the research used a causal-comparative design and collected data through a survey questionnaire with 260 participants. The study uses SPSS software and uses a quantitative exploratory research technique. The research found strong relationships with colleagues, training and development programs, and reward and recognition plan significantly increase employee productivity. However, the support of the supervisors has little impact.